2018
DOI: 10.1016/j.jenvman.2017.10.047
|View full text |Cite
|
Sign up to set email alerts
|

Fly ash classification efficiency of electrostatic precipitators in fluidized bed combustion of peat, wood, and forest residues

Abstract: The increasing use of biomasses in the production of electricity and heat results in an increased amount of burning residue, fly ash which disposal is becoming more and more restricted and expensive. Therefore, there is a great interest in utilizing fly ashes instead of just disposing of it. This study aimed to establish whether the utilization of fly ash from the fluidized bed combustion of peat, wood, and forest residues can be improved by electrostatic precipitator separation of sulfate, chloride, and some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
4
8
0
Order By: Relevance
“…When comparing these results to earlier published work [9,16,29,35], it can be seen that the achieved activity indexes are lower for classified fly ashes (Fig. 7) than for original fly ashes.…”
Section: Mortar Experimentssupporting
confidence: 62%
See 1 more Smart Citation
“…When comparing these results to earlier published work [9,16,29,35], it can be seen that the achieved activity indexes are lower for classified fly ashes (Fig. 7) than for original fly ashes.…”
Section: Mortar Experimentssupporting
confidence: 62%
“…However, this procedure requires water and energy for drying. Therefore, mechanical classification is one interesting option to improve fly ash chemical composition without the use of water, as there is a relationship between fly ash particle size and heavy metal, Cl − and SO 4 2 content [23][24][25][26][27][28][29][30][31]. It has been found that the utilization potential of fly ash from biomass and waste combustion can be significantly improved with mechanical classification [30].…”
Section: Introductionmentioning
confidence: 99%
“…These are the maximum allowed total concentrations of harmful elements (As, Cd, Cr, Cu, Ni, Pb, and Zn) and minimum concentrations of nutrients (Ca, K + P) using nitric-acid digestion. Most of the studies on ash fertilizers were conducted in Nordic countries, almost exclusively in Finland [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]. The typical viewpoint of most studies was to study the amount of pollutants in potential ash fertilizers and assess their environmental risks.…”
Section: Fertilizers and Soil Improversmentioning
confidence: 99%
“…The fractionation of fly ash to improve its quality for fertilizing purposes has been studied in a few papers with the target to separate harmful substances from the fly ash [48][49][50][51]58,61,76]. FBCFA is typically collected using electrostatic precipitators (ESP); therefore, Ohenoja et al [58], Dahl et al [49], and Orava et al [51] studied the use of electrostatic precipitators as classifiers of ash. Ohenoja et al [58] found that the harmful elements (As, Cd, and Pb) were enriched in the finest ash fraction collected from second and third ESP fields (particle size d 50 < 18 µm); therefore, the coarse ash from first field (d 50 > 18 µm) would be better suited for fertilizer use.…”
Section: Fertilizers and Soil Improversmentioning
confidence: 99%
See 1 more Smart Citation